Prevalence of Early Postnatal-Care Service Utilization and Its Associated Factors among Mothers in Hawassa Zuria District, Sidama Regional State, Ethiopia: A Cross-Sectional Study - Shambel Yoseph; Azmach Dache; Aregahegn Dona (Hindawi Limited, 2021)
Background. A postnatal care given after childbirth is a critical care to promote health and to prevent complications of the mother and newborn. However, utilization of this service is low in Ethiopia, and little is known about its coverage and determinants. Thus, this study aimed to assess the prevalence of early postnatal-care service utilization and its associated factors among mothers in Hawassa Zuria district, Sidama Regional State, Ethiopia. Methods. A cross-sectional study was conducted from 20 February to 20 March 2020 in Hawassa Zuria District among randomly selected 320 mothers. Data were collected by using interviewer-administered structured questionnaires. Data entered were into Epi data version 3.1 and exported to SPSS version 26 for analysis. Descriptive, bivariable, and multivariable logistic regression analysis with odds ratio and 95% confidence interval were conducted. A P value <0.05 was considered a statistically significant association. Finally, the results were presented by texts, tables, and figures. Result. The prevalence of early postnatal-care service utilization was 29.7% (95% CI = 24.7, 35.5). Age below 25 years [AOR = 3.2 (95% CI = 1.37, 7.48)], having planned and supported pregnancy for last birth [AOR = 2.2 (95% CI = 1.13, 4.38)], having information about obstetric danger signs [AOR = 2.1 (95% CI = 1.25, 3.78)], and having positive attitude on use postnatal services [AOR = 3.5 (95% CI = 1.94, 6.32)] were factors associated with early postnatal-care utilization. Conclusion. The finding revealed that early postnatal-care utilization in the study area was low. Strengthening family planning services, giving information on obstetrics danger signs, and creating awareness about postnatal care will improve uptake of the service in a timely manner.